Solar power - Oxlade, Chris (London : Raintree Publishers, 2013)
Examines the evolution of solar power, what it is, what it can do, and how it affects today's world.
What is solar power? -- Catching the Sun -- Heating with the Sun -- Solar electricity -- Solar power in space -- Solar power stations -- Solar transportation -- Solar power today -- Timeline -- Glossary.
Includes bibliographical references (p. 31) and index.
6.7
3-6.
3-6
Keywords: Solar energy -- Juvenile literature; Solar energy; Solar energy